Ginseng glucosyl oleanolate inhibit cervical cancer cell proliferation and angiogenesis via PI3K/AKT/HIF-1α pathway - Sitong Liu; Zhiyi Ai; Yue Hu; Guangquan Ren; Junshun Zhang; Ping Tang; Hongyang Zou; Xia Li; Yu Wang; Bo Nan; Yuhua Wang (npj Science of Food)
Abstract Ginseng (Panax ginseng C.A. Meyer) is widely used in several functional foods at present. Ginsenosides, is the most crucial bioactive constituents in ginseng whose antitumor activity have been widely reported. In this study, the effect of ginseng glucosyl oleanolate (GGO) produced from ginsenoside Ro through enzymatic transformation, on cervical cancer was evaluated in vitro and in vivo. GGO significantly inhibited the viability and colony forming ability of HeLa cells, and blocked the cell cycle in G0/G1 phase, which showed its ability to inhibit the proliferation of HeLa cells. GGO exhibited anti-angiogenesis effect in HUVECs, chick chorioallantoic membrane (CAM) and Matrigel plugs model. These effects were related to interference with the paracrine axis of VEGF/VEGFR2 and blockage of the downstream PI3K/AKT/HIF-1α signaling pathway of the autocrine axis. The dual inhibitory effects of GGO were also exhibited in immunocompromised mice undergoing heterograft and suppressed tumor growth without any side effects. These findings provide a theoretical basis for further development of GGO as a functional food with anti-tumor properties.